2015
DOI: 10.1186/s13104-015-1434-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical student opinions on character development in medical education: a national survey

Abstract: BackgroundRecently United States (US) medical schools have implemented curricular reforms to address issues of character in medical education. Very few studies have examined students’ opinions about the importance of character development in medical school. This cross-sectional study assessed US medical students’ opinions regarding character-focused education and their experiences receiving character feedback from educators. We mailed a questionnaire to 960 third year medical students from 24 medical schools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Carey et al ( 2015 ) investigated US medical students’ opinions on the character education they receive and find that medical students are generally receptive to character education 5 . However, what should such character education look like?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carey et al ( 2015 ) investigated US medical students’ opinions on the character education they receive and find that medical students are generally receptive to character education 5 . However, what should such character education look like?…”
Section: Discussionmentioning
confidence: 99%
“…While it is no doubt influential in theory, empirical study of virtue in medicine is in its infancy, with only a small body of empirical work in existence (e.g., Schulz et al 2013 ; Carey et al 2015 ). In fact, a recent review (Kotzee and Ignatowicz 2016 ), found that empirical study of medical ethical decision-making is still completely dominated by rule-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Several other studies also reported the feedbacks of students on teaching methodology and some also suggested for small group teaching method as a better strategy for better quality teaching. [16][17][18][19][20] …”
Section: Discussionmentioning
confidence: 99%
“…Evaluations recently concentrated on behaviors rather than attitudes as behavior and attitude may be irrelevant due to the context effect [29]. However, professional behavior is a complex issue demanding frequent measuring in various learning contexts through a combination of different methods and instrumentations [6].…”
Section: Comprehensive Model-based Educational Systemmentioning
confidence: 99%
“…Professional ethical competency is defined through two approaches including character-based approach and an approach concentrating on visible performance and professional behaviors [6]. The two are sometimes combined to provide a more comprehensive definition; in better words, professional ethical competency is indeed considered as a professional way of conducting oneself based upon values and commitment [7].…”
Section: Introductionmentioning
confidence: 99%